Examining the relationship between size and feeding preferences in the Caribbean spiny lobster Panulirus argus (Latreille, 1804) (Decapoda: Achelata: Palinuridae). Issue 2 (24th January 2018) - Gnanalingam, Gaya; Butler, Mark J
Abstract: Spiny lobsters are benthic predators whose selective predation may affect species composition and benthic community structure. With an increasing emphasis on the protection and conservation of heavily fished lobster populations, indirect effects on prey populations require greater consideration. Through a series of cafeteria trials, we investigated feeding preferences, consumption, and size selectivity in different sizes of Panulirus argus (Latreille, 1804). Our results demonstrate that small and large adult lobsters prefer different prey species. But unlike small lobsters that dominate in regions that are heavily fished, large lobsters are not restricted in the size of prey they can consume and they eat more prey than small lobsters. Fisheries and management practices that alter the size structure of lobster populations will therefore also affect prey community structure, but not necessarily to the detriment of prey that are of special ecological or fisheries value.